Effects on ventricular arrhythmias of oral captopril and of oral mononitrate started early in acute myocardial infarction: results of a randomised placebo controlled trial. Issue 2 (February 1993) - Pipilis, A; Flather, M; Collins, R; Hargreaves, A; Kolettis, T; Boon, N; Foster, C; Appleby, P; Sleight, P
Abstract : OBJECTIVE--To assess the effects of oral vasodilator treatment on ventricular arrhythmias in acute myocardial infarction. SETTING--Coronary care units at the John Radcliffe Hospital, Oxford, and the Royal Infirmary, Edinburgh. PATIENTS--100 patients with suspected acute myocardial infarction entered the study at a mean of 13 hours from symptom onset. DESIGN OF INTERVENTION--Double blind randomisation to 4 weeks treatment with captopril (12.5 mg three times a day after a 6.25 mg test dose (n = 32)) or isosorbide mononitrate (20 mg three times a day (n = 31)) or placebo control (n = 37). OUTCOME MEASURES--Ventricular arrhythmic events assessed by 48 hours of Holter monitoring starting at the time of randomisation. RESULTS--The number of ventricular extrasystoles/hour for captopril, mononitrate, and placebo was respectively (median and range) 6 (0-162), 4 (0-38), and 10 (0-932) (2p < 0.02 mononitrate v placebo). The number of episodes of multiple extrasystoles/hour was 0.2 (0-22), 0.3 (0-4), and 0.5 (0-19); (2p < 0.02 mononitrate v placebo). Episodes of ventricular tachycardia showed a non-significant decrease in the captopril and mononitrate groups (mean (SEM) 3.2 (0.8), 2.4 (0.7), and 4.7 (1.3) for the 48 hour period). The incidence of idioventricular rhythm was also reduced in both active treatment groups (28%, 19%, and 46% (2p < 0.05 mononitrate v placebo)). CONCLUSIONS--Oral mononitrate (and perhaps also captopril) seems to reduce the incidence of ventricular arrhythmias in the early phase of acute myocardial infarction. The effects on life-threatening arrhythmias, such as ventricular fibrillation, and on death can only be assessed in a much larger trial.